Analisis Teknik Sinematik Dalam Implementasi Color Grading Pada Film Dokumenter - M. Zainul Rohman; Aqsal Dzilham Aldito; M. Farman Andrijasa (Institute for Research and Community Service, 2024)
Purpose: Pampang Cultural Village, one of the Dayak cultural and tourism areas in Samarinda, East Kalimantan, Indonesia. The village has aesthetic educational value, especially related to the history, traditions, and cultural values of the ancestors that are still well preserved. However, at the cultural village art performance, there is a lack of young tourists who attend the traditional and cultural events of the Pampang Cultural Village, so it is necessary to have a documentary film by following the current trend style by using Cinematic Techniques applying Color Grading. Methods/Study design/approach: The method used in making the documentary is the Cinematic Technique by applying Color Grading. The use of Cinematic Techniques and Color Grading in the documentary is to create an aesthetic atmosphere that regulates lighting, shot types, and coloring so that the audience can describe the situation in the documentary. Result/Findings: The result of this research is a documentary film of Pampang Cultural Village which is used as a promotional medium for educational and aesthetic tourist attractions about the customs and culture of Kalimantan Island. Novelty/Originality/Value: The use of Cinematic Techniques and Color Grading in the documentary film is to create an aesthetic atmosphere that regulates lighting, shot type, and coloring. Keywords: Documentary Film, Pampang Cultural Village, Cinematic, Color Grading